Effects of Levosimendan on Cellular Metabolic Alterations in Patients With Septic Shock: A Randomized Controlled Pilot Study. Issue 3 (September 2017) - Hajjej, Zied; Meddeb, Bilel; Sellami, Walid; Labbene, Iheb; Morelli, Andrea; Ferjani, Mustapha
ABSTRACT: Introduction: Mitochondrial dysfunction and consequent cellular energetic failure play a key role in the development of sepsis-related organs failure. Evidence suggests that the pleiotropic effects of levosimendan may positively affect cellular metabolism during septic shock. Objectives: To investigate changes in the concentration of glucose, lactate, pyruvate, and glycerol in the extracellular fluid of the skeletal muscle following levosimendan administration in patients with septic shock. Methods: The study was designed as a prospective, double-blind, controlled, clinical pilot trial and performed in a multidisciplinary intensive care unit. After achieving normovolemia and a mean arterial pressure of at least 65 mm Hg, 20 septic shock patients were randomized to receive either levosimendan 0.2 μg/kg/min (n = 10), or dobutamine 5 μg/kg/min as active comparator (n = 10). Interstitial tissue concentrations of lactate, pyruvate, glucose, and glycerol were obtained by using muscle microdialysis. All measurements, including data from right heart catheterization, were obtained at baseline and every 6 h for the following 72 h after randomization. The trial is registered with Clinicaltrials.gov, number NCT02963454. Results: Compared with dobutamine, levosimendan increased interstitial tissue pyruvate concentration (153.3 ± 73 and 187. 2 ± 13.5 vs. 210.7 ± 76.2 and 161 ± 64.6; P  < 0.05), and lactate clearance (55 vs. 10). Lactate/pyruvate ratio was lower in the levosimendan group at the end of study period (37. 7 ± 18.9 and 29.3 ± 12.7 vs. 10.9 ± 4.5 and 31.4 ± 13. 2; P  < 0.05). Conclusion: Although we investigated a small number of patients, our preliminary results suggest that levosimendan may improve cellular metabolic alterations in patients with septic shock.